Development of a Training Program for Meta-Analytical Research: A Novel Approach to Minimizing Errors in Medical Systematic Reviews and Meta-Analyses - Palani, Ayad; Alipour, Hiva; Agarwal, Ashok; Crafa, Andrea; Saleh, Ramadan; Sahin, Bahadir; Shah, Rupin (Korean Soc Sexual Medicine & Andrology, 2025)
Purpose: The Global Andrology Forum (GAF) has developed an innovative training method to equip novice researchers with the fundamental skills to conduct high-quality systematic reviews and meta-analyses (SRMAs) under the supervision of senior experts. This article aims to describe and evaluate the effectiveness of the GAF training program in enhancing these skills. Materials and Methods: A six-module training program was designed to cover the key steps in SRMA studies, enabling GAF members to conduct high-quality SRMAs. Initially launched as a synchronous (remote) training program, it was later transitioned into an asynchronous format and implemented on the Moodle platform. Trainees participating in the synchronous training program were asked to evaluate the course using a specially designed questionnaire. Participants' assessments of the asynchronous course were collected at various stages. Data from both training models were statistically analyzed. Results: Among the trainees who participated in the questionnaire on the original synchronous course (n=101), the majority rated the material and assessments as clear, helpful, and effective in enhancing their knowledge. Additionally, the trainees indicated that the features offered in the training made them feel comfortable and engaged. Of the 29 participants enrolled in the asynchronous program, 22 took part in the assessment. Among them, 12 (54.5%) completed all course requirements, achieving an average score of 83.7%, qualifying them for conducting SRMAs. Conclusions: The GAF SRMA online training program has proven to be an effective and well-received initiative for equipping researchers with essential skills to conduct high-quality SRMAs. By addressing the diverse needs of trainees through its innovative and flexible design, the program has demonstrated its capacity to enhance knowledge and engagement. The successful implementation of this training program highlights its potential to significantly improve the quality of SRMAs in medical research, thereby contributing to the advancement of evidence-based medical practice on a broader scale.
Durairajanayagam, Damayanthi/0000-0001-9049-0215; Dardmeh, Fereshteh/0000-0002-2034-0147; Çeker, Gökhan/0000-0002-7891-9450; Dimitriadis, Fotios/0000-0003-1198-9144; Palani, Ayad/0000-0001-7806-9903; Aiansjah, Ricky/0000-0002-9733-3092; Crafa, Anea/0000-0002-8311-9095; Ceyhan, Erman/0000-0001-8223-6399
Keywords: Learning; Distance; Meta-Analysis; Systematic Review; Teaching